Research on technological innovation and marketing publicity decision of green intelligent home appliance supply chain considering consumer subsidy and cost-sharing contract - Che, Cheng; Li, Qing; Yin, Qi; Li, Suhui; Zheng, Huixian; Geng, Xin (Frontiers in Energy Research, 2023)
Under the leadership of China's "dual carbon" policy, how to reduce energy consumption, reduce carbon emissions, and realize intelligent, low-carbon development has become a key issue facing the home appliance industry. Studies have shown that green intelligent home appliances can save electricity and reduce carbon emissions. In the context of China's "dual-carbon" goal, this study examines the technological innovation and marketing publicity decisions of the green intelligent home appliance supply chain considering consumer subsidy and cost sharing contract. By constructing a three-level supply chain model including home appliance manufacturers, retailers, and consumers, we use the Stackelberg game method to study the decision-making models under four scenarios with and without consumer subsidy and cost sharing contract, and consider the impact of consumers' green intelligent preference, consumers' green marketing sensitivity, consumer subsidy and cost sharing contract on the supply chain optimal decision. Through model solving and further numerical simulation, the results show that: (1) The increase of consumers' green intelligent preference and consumers' green marketing sensitivity can produce positive spillover effects, and promote the improvement of home appliance manufacturers' technological innovation efforts and retailers' marketing publicity efforts; (2) Consumer subsidy is always beneficial for the green intelligent development of the supply chain, which can effectively increase the total revenue of the supply chain; (3) The reasonable cost sharing ratio can stimulate the enthusiasm of supply chain enterprises to increase technological innovation and marketing publicity investment, and increase the total profit of the supply chain. However, the excessive cost sharing ratio frustrates the enthusiasm of home appliance retailers to participate in the coordination, resulting in a decline in the overall benefit of the supply chain; (4) Considering both consumer subsidy and cost sharing contract, a reasonable level of consumer subsidy amount and cost sharing ratio have a better incentive effect on supply chain members than the other three scenarios. This study can provide a broader reference for the green intelligent development of China's home appliance industry, which has an important role in the implementation of China's "dual carbon" goal.